2021
DOI: 10.16970/entoted.770859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spinosad, azadirachtin and kaolin on Stephanitis pyri (Fabricius, 1775) (Hemiptera: Tingidae) under laboratory conditions

Abstract: This study was conducted in Diyarbakır (Turkey) in 2019 to determine the effects of natural insecticides, spinosad, azadirachtin and kaolin, on the fourth instar nymphs and adults of Stephanitis pyri (Fabricius, 1775) (Hemiptera: Tingidae). The study was conducted under the laboratory conditions; 25 ± 1ºC, 65 ± 5% humidity and 16:8 h L:D photoperiod. The mortality of nymphs 3 and 6 d after treatment with spinosad, azadirachtin and kaolin was 49, 44 and 11%, and 54, 51 and 47%, respectively. The mortality of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(23 reference statements)
0
4
0
1
Order By: Relevance
“…Kowalska (2008) noted that all concentrations of spinosad (0.2%, 0.1% and 0.05%) caused mortality both Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae) adults and larvae depending on the temperature. Maral (2021) reported that, the highest mortality rate of Stefanitis pyri (Fabricius) (Heteroptera: Tingidae) adults was found in spinosad after that azadirachtin and kaolin. In this study, the effect of azadirachtin varied depending on the rate of active substance, dose and incubation period.…”
Section: Resultsmentioning
confidence: 99%
“…Kowalska (2008) noted that all concentrations of spinosad (0.2%, 0.1% and 0.05%) caused mortality both Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae) adults and larvae depending on the temperature. Maral (2021) reported that, the highest mortality rate of Stefanitis pyri (Fabricius) (Heteroptera: Tingidae) adults was found in spinosad after that azadirachtin and kaolin. In this study, the effect of azadirachtin varied depending on the rate of active substance, dose and incubation period.…”
Section: Resultsmentioning
confidence: 99%
“…Ülkemizde Tingidae familyasına bağlı türlerle ilgili olarak, çeşitli sörveyler esnasında, daha çok tür tespitlerinin yapıldığı çalışmalar (Önder ve Lodos, 1983;Bolu, 2007;Aysal ve Kıvan, 2011;Maral ve ark., 2013;Yıldırım ve ark., 2013;Küçükbasmacı, 2014;Dursun ve Fent, 2017;Yücel ve Kıvan, 2018) ile bazı türlerin yayılışları, zararları, biyolojileri ve mücadeleleri hakkında araştırmalar bulunmaktadır (Gülperçin ve Önder, 1999;Aysal, 2008;Aysal ve Kıvan, 2007, 2018bKıvan ve Aysal, 2011;Maral, 2021;Aysal ve Sağlam, 2022). Ancak doğal düşmanlarının belirlenmesine yönelik çalışmaların sınırlı sayıda olduğu dikkat çekmektedir (Önder ve ark., 1986;Bolu, 2007;Kıvan ve Aysal, 2009;Maral, 2012;Maral ve ark., 2014Maral ve ark., , 2020.…”
Section: Introductionunclassified
“…Adults and nymphs feed on the lower surface of apple leaves, causing visible spots on the upper surface of the leaf, as well as the presence of insect feces in the form of black spots on the lower surface of the leaf. And that the infection affects the photosynthesis process as well as has an effect on the process of respiration and leads to early leaf fall [4]. Many studies have shown that the suitability of the plant host for the growth, development and reproduction of pests is not limited to the variation of the types of these plant hosts only, but also to the differences between the varieties of the same species.…”
Section: Introductionmentioning
confidence: 99%